SYLLABUS DESIGN FOR COMMUNICATIVE COMPETENCE IN LANGUAGE TEACHING - Astawa I Nengah; Wersi Murtini Ni Made; Wardana I Ketut (Program Studi Pendidikan Bahasa Inggris FKIP Universitas Mahasaraswati Denpasar, 2021)
Communicative competence approach in Indonesia has been applied in junior and senior high school. It emerged due to the fact that the audio-lingual approach has been regarded to be a failure. This can be seen from the graduates’ inability to use the language for communication in real situations. It is said that this approach is very successfully applied in Europe; but in Indonesia, it is still a big question, since the situation and condition are very much different from that of European countries. The obstacles existing in Indonesia are; big classes, linguistic environment, teachers’ inability to use English, time allotment, etc. One thing for sure is that however successful an approach in some developed countries is, it is quite possible this approach might be a failure when applied in Indonesia due to some different conditions and situations as stated above. Consequently, it is advisable for the English teachers to be selective in choosing which approach is suitable for teaching what so that we do not always get confused with the mode of language teaching which very often changes in foreign countries.